How are sports-trackers used by runners? Running-related data, personal goals, and self-tracking in running - Karahanoglu, A.; Gouveia, R.; Reenalda, J.; Ludden, G. (Sensors, 2021)
The purpose of this research is to explore the roles that sports trackers and running-related data play in runners` personal goal achievement. A two-week diary study and semi-structured interviews were conducted with 22 runners to explore how runners engage with their running-related data to set and achieve their running goals. We found that participants pursued and transitioned between different running goals as their needs, abilities, and surrounding environment changed. We also found multiple motivations that shaped the use of sports trackers. We identified two main categories in runners` motivations for using trackers and data to achieve their goals. These categories were (i) documenting and tracking in running, and (ii) supporting goal-oriented reflections and actions, with various reasons for use while preparing for and during running. This study provides insights into the psychological effects of running-related data and signals practical implications for runners and developers of tracking technology.